Multinational financial management - Shapiro, Alan C. (Hoboken: Wiley, 2020)
"Multinational Financial Management, 10th Edition provides corporate managers with a conceptual framework within which the key financial decisions of the multinational firm can be analyzed. It contains charts and illustrations of corporate practice that are designed to highlight specific techniques. Numerous real-world examples and vignettes provide actual applications of financial concepts and theories. Seven longer illustrations of actual company practices appear at the end of key chapters to demonstrate different aspects of international financial management. Corporate managers will also benefit from the mini cases in each chapter that illustrate important concepts"--
Includes bibliographical references and index.
Keywords: International business enterprises -- Finance; BUSINESS & ECONOMICS / Corporate Finance